Halonium-Induced Polyene Cyclizations - D’Hollander, Agathe C. A.; Peilleron, Laure; Grayfer, Tatyana D.; Cariou, Kevin (Synthesis, 2019)
This review covers the methods that chemists have developed to access halogenated polycyclic structures from polyenes, by emulating Nature’s enzymatic machineries. From pioneering studies to the most recent developments, the different strategies, whether based on the use of standard reagents or on the design of specific ones, will be presented. Finally, asymmetric reactions and applications for the total synthesis of natural products will be exposed.1 Introduction2 Pioneering Studies3 Use of Specific Reagents4 Use of N-Haloamides5 Asymmetric Reactions6 Total Synthesis of Halogenated Natural Products7 Conclusion and Perspectives
Keywords: halogenation; polyenes; biomimetic synthesis; cascade cyclization; asymmetric synthesis; natural products